BS ISO 27145-2 AMD 1. Road vehicles. Implementation of World-Wide Harmonized On-Board Diagnostics (WWH-OBD) communication requirement. Part 2. Common data dictionary (14th February 2023) - British Standards Institution,
No abstract available